Gabby's practical English-Filipino dictionary - Gaboy, Luciano Linsangan 1954- (Milmar Soyuz Trading, 1999)
A dictionary that contains entries in English and Filipino, along with their corresponding meaning or equivalent in Filipino which provides the closest translations to the import of the English word, pronunciations, spellings and hyphenation. It also has information on the dialects and cultural groups in the Philippines, as well as some of the languages of the world.